2018
DOI: 10.1111/ane.12963
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly increasing off-label use of rituximab in multiple sclerosis in Sweden - Outlier or predecessor?

Abstract: The share of MS patients in Sweden who are treated with rituximab is very high, and also rapidly increasing. Taken into account the off-label use, cases with adverse medical conditions that could possibly be related to rituximab use should be reported thoroughly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
1
44
1
4
Order By: Relevance
“…Second line treatments include fingolimod and natalizumab 60 . In addition to the recommended first line treatments, Rituximab is often prescribed off label, meaning there is limited information on the long term safety and efficacy of this treatment for MS patients 61 . When and how to make the transition from first line to second line treatment can be difficult, with no internationally recognised guidelines on when the decision should be taken and how it should be implemented 62 .…”
Section: Treatment Of Msmentioning
confidence: 99%
“…Second line treatments include fingolimod and natalizumab 60 . In addition to the recommended first line treatments, Rituximab is often prescribed off label, meaning there is limited information on the long term safety and efficacy of this treatment for MS patients 61 . When and how to make the transition from first line to second line treatment can be difficult, with no internationally recognised guidelines on when the decision should be taken and how it should be implemented 62 .…”
Section: Treatment Of Msmentioning
confidence: 99%
“… 1 Rituximab (RTX), a first-generation anti-CD20 mAb, has also been adopted as an off-label treatment in MS, 2 , 3 and it is currently used as standard of care therapy in some European countries. 4 The standard treatment regimen of anti-CD20 mAbs usually consists of an “induction” phase, followed by regular fixed maintenance reinfusions (usually every 6 months). However, despite being a more practical approach in the daily practice, the fixed doses regimen could represent an overtreatment because B cells could be still depleted before each subsequent retreatment dose, as B cell immune reconstitution after B cell depletion ranges from 27 to 125 weeks with a median of 72 weeks.…”
mentioning
confidence: 99%
“…As pointed out in our introduction, there is a rapid increase in the use of RTX for MS in Sweden, not only as an alternative when previous DMT was ineffective, but also as a first‐line therapy. By June 2017, over 50% of all treatment naïve subjects with MS in Sweden received RTX as their first DMT . This growth has recently resulted in the Swedish Ministry of Health and Social Affairs planning a risk‐benefit analysis of off‐label RTX use, underlining the importance of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sweden stands out with its high use of off‐label rituximab (RTX), representing approximately 40% of all ongoing DMTs in MS care . Furthermore, a Swedish study that included subjects with MS from three tertiary academic hospitals showed that as many as 53.3% of all subjects were given RTX as the primary DMT for MS . The published data extracted from the Swedish MS registry show increased off‐label use of RTX for both relapsing‐remitting MS (RRMS) and progressive disease (PMS).…”
Section: Introductionmentioning
confidence: 99%